Innovation in East Asia diversity and development - Hobday, Mike
The author suggest that the so-called 'flying geese' model of East Asian development fails to capture the diversity of development paths in that region, particularly for South Korea, Taiwan, Hong Kong and Singapore. The case is argued for a new model accepting the importance of Japan but also examining other major factors in the region's development.
Following Japan, the four 'tigers' or newly industrialising countries (NICs) of East Asia (South Korea, Taiwan, Hong Kong and Singapore) have made remarkable strides in terms of economic growth, per capita incomes and technological progress. Some observers attribute the growth of the NICs and other neighbouring East Asian economies (e.g. China, Malaysia, Thailand and Indonesia) mainly to Japan. This view is expressed in the so-called 'flying geese' model of East Asian development. This paper argues that although Japan is undeniably important, the flying geese model fails to capture the diversity of development paths in the region. The four NICs are an important and distinct source of East Asian technological progress, competitiveness and regional investment. The flying geese model also underplays the significance of the US economy, both as a market and as a source of technology and investment. The paper argues that there is a case for a new model of East Asian development; one which accepts the importance of Japan, but also recognises and explores the other significant factors in the region's development.
Keywords: Innovation--East Asia